2022
DOI: 10.5935/0103-507x.20220026-en
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of central venous minus arterial carbon dioxide pressure to arterial minus central venous oxygen content ratio and lactate levels as predictors of mortality in critically ill patients: a systematic review and meta-analysis

Abstract: Objective The central venousarterial carbon dioxide pressure to arterial-central venous oxygen content ratio (P cv-a CO 2 /C a-cv O 2 ) is frequently used as a surrogate for tissue oxygenation. We aimed to identify and synthesize literature and quality of evidence supporting P cv-a CO 2 /C a-cv O 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
(83 reference statements)
0
2
0
Order By: Relevance
“…Several recent studies have highlighted the potential prognostic markers of outcome in severe sepsis, including the central venous minus arterial carbon dioxide pressure to arterial minus central venous oxygen content ratio (Pcv-aCO2/Ca-cvO2 [141,142], the CRP/albumin ratio [86,143], and lactate clearance [65,113,116,144]. The diagnostic performance of the Pcv-aCO2/Ca-cvO2 ratio > 1.696 at 24 h was analyzed using the ROC curve, and it was found to have an AUC of 0.82 (95% CI, 0.661-0.979).…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have highlighted the potential prognostic markers of outcome in severe sepsis, including the central venous minus arterial carbon dioxide pressure to arterial minus central venous oxygen content ratio (Pcv-aCO2/Ca-cvO2 [141,142], the CRP/albumin ratio [86,143], and lactate clearance [65,113,116,144]. The diagnostic performance of the Pcv-aCO2/Ca-cvO2 ratio > 1.696 at 24 h was analyzed using the ROC curve, and it was found to have an AUC of 0.82 (95% CI, 0.661-0.979).…”
Section: Discussionmentioning
confidence: 99%
“…The ability of P cv-a CO 2 /C a-cv O 2 as a predictor of outcomes in critically ill patients has been extensively reviewed elsewhere [ 88 ]. More than twenty years ago, a retrospective study performed in 89 patients monitored with a Swan–Ganz catheter found that a value of P mv-a CO 2 /C a-mv O 2 higher than 1.4 was a predictor of hyperlactatemia and mortality [ 74 ].…”
Section: Venous Minus Arterial Carbon Dioxide Partial Pressure To Art...mentioning
confidence: 99%